The interleukin-6, serotonin transporter, and monoamine oxidase A genes and endurance performance during the South African Ironman Triathlon - de Milander, L.; Stein, D. J.; Collins, M. (Applied Physiology, Nutrition, and Metabolism, 2009)
Previous studies have identified an association of genetic variants believed to alter physiological and biochemical processes locally within the skeletal muscle and therefore performance in the Ironman triathlon. There is growing evidence that the serotonergic system and circulating interleukin (IL)-6 levels are also involved in mediating endurance capacity. Investigators have demonstrated that recombinant human IL-6 administration and serotonergic neurotransmission manipulation, with 5-hydroxytryptamine transporter (5-HTT) and monoamine oxidase A (MAO-A) inhibitors, prior to exercise, can alter running performance, consistent with a central governor hypothesis. The aim of this study was to investigate possible associations of functional polymorphisms within the IL-6, 5-HTT, and MAO-A genes with endurance performance of Ironman triathletes. Four hundred sixty-eight male Caucasian triathletes who completed the 2000 and (or) 2001 South African Ironman Triathlon and 200 healthy Caucasian male controls were genotyped for the -174 IL-6 G/C, 5-HTT 40 base pair (bp) insertion-deletion and 30 bp variable number of tandem repeats (VNTR) MAO-A gene polymorphisms. There were no significant differences in the relative genotype distributions within the IL-6 (p = 0.636), 5-HTT (p = 0.659), and MOA-A (p = 0.227) polymorphisms when the fastest-fnishing, middle-finishing, and slowest-finishing triathletes, as well as the control groups, were compared. There were no direct associations between the IL-6 -174 G/C, 5-HTT 44 bp insertion-deletion, and MAO-A 30 bp VNTR gene polymorphisms and endurance performance in the 2000 and (or) 2001 South African Ironman Triathlons. The neurogenetic basis of the central governor requires further investigation.